1977
DOI: 10.1002/ajpa.1330470314
|View full text |Cite
|
Sign up to set email alerts
|

Number of epidermal melanocytes, hair follicles, and sweat ducts in skin of Solomon Islanders

Abstract: The number of epidermal appendages and melanocytes in forearm skin of three groups of Solomon Islanders has been determined. There were no significant differences in the number of hair follicles or sweat ducts among Solomon Islander groups, nor between them and a Caucasian group used for comparison. The Nasioi and Kwaio, however, do have a significantly higher melanocyte population than Caucasian groups. This difference may in part be due to the exposure of the Solomon Islander skin used in this study to chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Needless to say, this is an oversimplification of the phenomenon of melanin, skin pigmentation and complexion coloration. It has been shown that within the epidermis the quantity and type of melanin, and the pattern of melanosome distribution, rather than the number of melanocytes, comprise the primary determinants of colour 12–15 . The distribution patterns of melanosomes in dark and light skin as in African/American individuals and Caucasians are well documented and have been described by various authors in a matter‐of‐fact manner.…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, this is an oversimplification of the phenomenon of melanin, skin pigmentation and complexion coloration. It has been shown that within the epidermis the quantity and type of melanin, and the pattern of melanosome distribution, rather than the number of melanocytes, comprise the primary determinants of colour 12–15 . The distribution patterns of melanosomes in dark and light skin as in African/American individuals and Caucasians are well documented and have been described by various authors in a matter‐of‐fact manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used these data as the basis for ethnic comparisons. For example, Garcia et al (1977) compared the skin biopsy samples of three racial groups from the Solomon Islands (N ¼ 5, 19, 5) with these data. They found no differences in the number of eccrine sweat glands (per unit area) among the ethnic groups, or between them and the Caucasian sample (N ¼ 5).…”
Section: In Sudomotor Capacitymentioning
confidence: 99%
“…This is performed using skin samples obtained during surgical procedures [67], collected via skin biopsies [68] or harvested from cadavers [69]. It appears that about 5%–10% of these anatomical glands are made up from normally developed, yet inactive sweat glands [65,66].…”
Section: Reviewmentioning
confidence: 99%
“…About 5%–10% of these glands are physiologically inactive [65,66]. Sources: Krause [23], Szabo [67], Garcia et al [68], Hwang and Baik [69], Glaser [83] and Cauna [84]. Calculations: Glandular density for each region was derived as follows: regional density = (( N 1 × density 1 ) + ( N 2 × density 2 ) + … ( N i × density i )) / N Total (where N is the sample size and subscript numerals refer to separate studies).…”
Section: Reviewmentioning
confidence: 99%